Chemical constituents of tobacco smoke induce the production of interleukin-8 in human bronchial epithelium, 16HBE cells. Issue 1 (December 2016) - Zhou, Guojun; Xiao, Weiqiang; Xu, Chengyun; Hu, Yajun; Wu, Xiaokai; Huang, Fangfang; Lu, Xinbo; Shi, Chunyun; Wu, Ximei
Abstract Background Interleukin-8 (IL-8) functions as a major chemoattractant and plays pivotal roles in the initiation and development of chronic obstructive pulmonary disease (COPD), and tobacco smoke is a most risk factor contributing to the development of COPD. Hence, we have screened some of the tobacco smoke-derived chemical compounds that potentially induce the production of IL-8 in human bronchial epithelium, 16HBE cells. Methods Twenty-eight hazardous smoke components belonging to 9 classes including nicotine, ammonia, aromatic amines, polycyclic aromatic hydrocarbons, phenols, carbonyls, hydrocyanic acid, nitrosamines and other volatile organics were used in the experiments. Proliferation of 16HBE cells was determined by cell counting kit-8 kit, luciferase activity was measured inIL-8 reporter gene-expressing 16HBE cells, and IL-8 levels in culture supernatants were quantified by enzyme-linked immunosorbent assay. Results At the non-toxic dosages, chemical compounds belonging to nicotine, aromatic amines, benzopyrene, phenols, aldehydes, and some other volatile organics dose-dependently increasedIL-8 reporter gene expression. Consistently, the representative compounds belonging to nicotine, aromatic amines, benzopyrene, phenols, aldehydes, and some other volatile organics significantly and dose-dependently increased IL-8 levels in the culture supernatants of 16HBE cells, among these compounds, benzopyrene is a most potent stimulator for inducing IL-8 production. Conclusions The present study has identified particular tobacco smoke constituents responsible for inducing the IL-8 production in human bronchial epithelium, which might help shed light on the pathogenesis of tobacco smoke-induced COPD.